Analisis Kinerja Jalan Seth Adjie Kota Palangka Raya - Juliano Malendra; Desriantomy; Murniati (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
Side barriers are the impact on traffic performance from roadside activities, such as pedestrians, parkedvehicles/vehicles stopping, vehicles entering/exiting, and slow vehicles. This traffic problem occurs on SethAdjie Street, Palangka Raya City, this is caused by the high economic and social activity on that road. Thisstudy aims to determine the effect of side barriers on road capacity and traffic speed due to road performance,as well as evaluate the level of service using the Indonesian Road Capacity Guidelines (2014). This researchwas carried out for 7 days in July 2022. Research data was obtained through surveys and direct measurementsin the field. The results obtained in segment 1 Side Barriers were 510.5 events per hour/200 m, Capacity (C)was 1922.37 cur/hour, Traffic Speed (VT) was 14.84 km/hour. Segment 2 Side Barriers of 389 events perhour/200 m, Capacity (C) of 2537.24 cur/hour, Traffic Speed (VT) of 20.39 km/hour. Segment 3 Side Barriersof 507 events per hour/200 m, Capacity (C) of 2298.41 cur/hour, Traffic Speed (VT) of 16.35 km/hour. Insegments 1 and 3 Service Level C and segment 2 Service Level B. With recommendations for the addition oftraffic signs and parking prohibition signs.